Two new crane fly species of the subgenus Vestiplex Bezzi, 1924 (Diptera, Tipulidae, Tipula) from Yunnan and Sichuan, China, with a key to species in the immota species group - Qiu-Lei Men; Pavel Starkevich; Aidas Saldaitis (ZooKeys, 2021)
Two new crane fly species, Tipula (Vestiplex) gongdangensis sp. nov. and T. (V.) dechangensis sp. nov. are described and illustrated based on materials collected in the Yunnan and Sichuan provinces, China. A key is provided to distinguish males of the new species from those of other species in the T. (V.) immota Alexander, 1935 species group which is proposed here for the first time.